2010
DOI: 10.4103/0255-0857.66484
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an in-house latex agglutination test with IgM ELISA and MAT in the diagnosis of leptospirosis

Abstract: The laboratory diagnosis of leptospirosis is fraught with several problems. Isolation of Leptospira by culture has a low sensitivity and the microscopic agglutination test (MAT) is time consuming To overcome these problems, a rapid latex agglutination test (LAT) has been standardized for the detection of antileptospiral antibodies in serum samples from suspected cases of leptospirosis. We compared the efficiency of the LAT to a commercially available IgM ELISA and MAT. A total of 150 serum samples were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
1
4
0
2
Order By: Relevance
“…[10] MAT is considered as the gold standard for serodiagnosis of leptospirosis, but in previous studies its sensitivity was found to vary from 30% to 76%, with a specificity of 97%. [11] But in combination, the sensitivity of IgM ELISA and MAT was found to increase to 70% as reported earlier by Shekathkar et al [12] Several recombinant proteins (rLipL32, rLipL41) have been identified to be specific to pathogenic leptospires, but with varied sensitivity and specificity in serodiagnosis. One such recombinant protein LipL32 IgG ELISA, the sensitivity and specificity was 96.2% and 90% respectively, which was comparable with Pan Bio IgM ELISA.…”
Section: Discussionsupporting
confidence: 65%
“…[10] MAT is considered as the gold standard for serodiagnosis of leptospirosis, but in previous studies its sensitivity was found to vary from 30% to 76%, with a specificity of 97%. [11] But in combination, the sensitivity of IgM ELISA and MAT was found to increase to 70% as reported earlier by Shekathkar et al [12] Several recombinant proteins (rLipL32, rLipL41) have been identified to be specific to pathogenic leptospires, but with varied sensitivity and specificity in serodiagnosis. One such recombinant protein LipL32 IgG ELISA, the sensitivity and specificity was 96.2% and 90% respectively, which was comparable with Pan Bio IgM ELISA.…”
Section: Discussionsupporting
confidence: 65%
“…2001; Shekatkar et al . 2010; Raja and Natarajaseenivasan 2015) either as a single (Dey et al 2007; Senthilkumar et al . 2008a; Deneke et al .…”
Section: Introductionmentioning
confidence: 99%
“…The outer membrane (transmembrane, peripheral and lipoproteins) proteins (OMPs) of Leptospira play a vital role in maintaining the cell structure and pathogenesis of leptospirosis besides diagnostic or immunogenic markers (Haake and Zuckert 2015;Raja and Natarajaseenivasan 2015). Several researchers evaluated the potential use of recombinant OMPs of pathogenic Leptospira in various immunodiagnostic assays (Smits et al 2001;Shekatkar et al 2010;Raja and Natarajaseenivasan 2015) either as a single (Dey et al 2007;Senthilkumar et al 2008a;Deneke et al 2014;Nagalingam et al 2015) or in combination with other proteins (Alizadeh et al 2014;Ye et al 2014) for the detection of anti-leptospiral antibodies for serodiagnosis. Generally, these recombinant antigen-based tests are safe and better alternatives to live cultural antigens for serodiagnosis of leptospirosis.…”
Section: Introductionmentioning
confidence: 99%
“…Considering MAT as reference and compared with various rapid tests, SD leptospira shows higher sensitivity, specificity, PPV, NPV and accuracy values 72.7%, 70.1%, 54.5%, 83.9% and 71% respectively as both MAT and SD leptospira tests detects IgG antibodies appearing later during the course of disease. In S Shekatkar et al,study showed the sensitivity and specificity of Latex agglutination test was 90.62% and 91.96% respectively compared to MAT (gold standard) which was slightly lower in our study that sensitivity and specificity of LAT was 84.8% and 70.1% respectively [13].…”
Section: Referencesmentioning
confidence: 51%